Análisis de problemáticas amazónicas en la narrativa de Jaime Vásquez Izquierdo desde el enfoque del desarrollo integral según Mario Bunge Iquitos 2024 - Marticorena Quintanilla, Manuel Ranulfo (2024)
The preparation of the thesis "Analysis of Problems in the Narrative of Jaime Vásquez Izquierdo from the Perspective of Development According to Mario Bunge, Iquitos 2024" aims to analyze the representations of Amazonian issues in the five novels of Jaime Vásquez Izquierdo, to understand how these literary narratives reflect and can contribute to the integral and sustainable development of the Amazon region, in line with the theoretical conception of development proposed by Mario Bunge. For this purpose, a qualitative, documentary, interpretative methodology and specialized survey were used. The result is evidence of biological problems (human health), economic problems (the national budget does not reach its destination, cut and appropriated by authorities and administrators), cultural problems related to social discrimination (from non-Loreto people towards Loreto people and ancestral cultures), prostitution caused by economic factors, Amazonian patriotism present in Loreto people but ignored by non-Loreto people, widespread corruption and injustice, and deficient education. Additionally, the political problem reflected in corruption and the misery in which the inhabitants live. It concludes that the Peruvian Amazon is unknown to Peruvian centralism and its authorities plagued by corruption and personal interests that will not solve the various problems unless the Amazon is scientifically known and there is awareness to solve the problems of its society for the good of the country.